2007 IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications 2007
DOI: 10.1109/pimrc.2007.4394738
|View full text |Cite
|
Sign up to set email alerts
|

BEAR: A Bursty Error Auto-Regressive Model for Indoor Wireless Environments

Abstract: In this paper we propose a novel channel model for indoor wireless environments. Using a set of real measurements, we tune the parameters of an Auto-Regressive filter, which is the core of the proposed model; furthermore we assess that its behavior is much closer to real wireless links that those exhibited by some of the most currently used approaches. The novel channel model is integrated within the framework of the Network Simulator environment. Its goal is to mimic the "bursty" behavior that characterizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In [5] it is shown that, under slow fading conditions, the SNR (Signal to Noise Ratio) of indoor wireless channels can be well approximated by an autoregressive (AR) model. This means that, under such conditions, we can model the channel attenuations as…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In [5] it is shown that, under slow fading conditions, the SNR (Signal to Noise Ratio) of indoor wireless channels can be well approximated by an autoregressive (AR) model. This means that, under such conditions, we can model the channel attenuations as…”
Section: Modelmentioning
confidence: 99%
“…Therefore, we are allowed to formulate the game as a stochastic game in which each user j controls its own Markov chain on the state space 5j. As in the single user case 5j is the set of all the possible states (5). Formally, the state space of the stochastic game at hand is the Cartesian product 5* = 51 X 52 .…”
Section: Multi User: Stochastic Game Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bursty Error model based on Auto-Regressive filter (BEAR) is able to adequate channel behavior depending on link quality, in terms of the received SNR per frame, and thus it can be used to study cross layer optimization techniques, as the one we are analyzing in this paper. BEAR is able to precisely reflect the behavior of typical office environments, especially in terms of the appearance of erroneous frame bursts [12], [15], which are quite likely to happen within real propagation conditions and may have a strong impact over the ETX estimation, as reported in [8].…”
Section: Channel Model For Indoor Wireless Linksmentioning
confidence: 99%
“…Since states are normally distributed, the objectives of exploitation and exploration naturally correspond to the conditional mean and variance of an arm, which at the same time contain all relevant information concerning its state (and thus fully describe the belief state of the arm). The AR(1) model has been found useful for example for modeling channels in wireless networks [1]. It seems that in the context of decision making under reward observability it has previously only been considered in [3], where the myopic (greedy) policy was compared numerically to an ad hoc randomized policy.…”
Section: Introductionmentioning
confidence: 99%